Quantitative Determination of 18-β-Glycyrrhetinic Acid in HepG2 Cell Line by High Performance Liquid Chromatography Method - Giuseppina Nocca; Cinzia Callà; Stefano Angelo Santini; Adriana Amalfitano; Luca Marigo; Diana Valeria Rossetti; Gianrico Spagnuolo; Massimo Cordaro (International Journal of Analytical Chemistry)
A reverse phase high performance liquid chromatographic (RP-HPLC) method was developed for identification and estimation of 18-β-glycyrrhetinic acid (GA) in HepG2 cell line. The analysis was carried out using a JASCO HPLC system with a C-18 (3 μm) Supelco reversed phase column (150 x 4.7 mm) using a mobile phase of 80% CH3OH and 20% of CH3CN: tetrahydrofuran: water (10:80:10, v/v/v). The method was linear in the concentration range of 1.5–120 μg /mL (n = 5). The LOD and LOQ were determined based on standard deviation of the y-intercept and the slope of the calibration curve. The LOD and LOQ values were found to be 11.46 μg/mL and 34.72 μg/mL, respectively. The mean percentage recovery by standard addition experiments of GA is 92.4 % ± 5.2%. The intracellular GA concentration value, obtained as mean of five different determinations, was 45.8 ± 7.45 μg/mL. We have developed a HPLC-UV method for quantitative determination of GA inside cells, with advantages in the cost reduction and economy of the analytical process.